Digital Competence of Society for Online Crowdfunding Acceleration in West Java - Alifa, Nabiela Rizki; Sutisna, Fajar Andrian (West Science Social and Humanities Studies, 2025)
Digitalization has become a disruption worldwide, including in Indonesia. One dominant aspect of this phenomenon is digital transactions. Bank of Indonesia (BI) reported that the cumulative value of electronic money transactions for the period of January to August 2024 reached IDR 1.6 quadrillion, representing a 35.76% growth compared to IDR 1.18 quadrillion (yoy). This highlights the role of digital transactions as a solution and convenience for various activities, including online crowdfunding. Crowdfunding is a rooted culture in Indonesia and demonstrates sustainable economic benefits in West Java. This activity does not always run smoothly, as issues arise within crowdfunding management institutions, leading to societal trust issues. Based on this phenomenon, strengthening the digital ecosystem in West Java is worthy of study. This research aims to measure society's digital competence level about digital transaction activities, particularly crowdfunding. This research uses a descriptive analysis method with a quantitative approach. Primary data from 258 respondents were obtained through questionnaire distribution targeting urban and rural communities in West Java was employed. The data were analyzed using simple regression analysis. The results show that the level of digital competence in society is not yet optimal; however, digital competence significantly influences digital transaction activities positively. Therefore, exploration is needed to establish credible crowdfunding management in West Java.